Chemical composition of selected manganese nodules from northeastern equatorial Pacific using X-ray emission spectrometry - Greenslate, J L; Fisk, Mary B; Felix, D (PANGAEA, 2023)
Selected manganese nodules from the DEEPSONDE and BENTHIFACE expeditions conducted by the Scripps Institution of Oceanography (SIO) in the northeastern equatorial Pacific have been analysed using X-ray emission spectrometry.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment